Numerical Investigation of the Behavior of Unstiffened Semi-Rigid Top and Seat Angle Connections under Monotonic Loading - Alemdar, Zeynep Firat; Balaban, Yusuf (MDPI, 2023)
In steel structures, unstiffened top and seat angle connections (TSACs) show semi-rigid behavior and transfer both the vertical reaction and some end moment of the beam while also making some degree of rotation. The moment-rotation behavior of TSACs has been evaluated using experimental and numerical analyses under monotonic loading and generally compared in the linear elastic region. In this paper, three-dimensional (3-D) finite element models of the TSACs were developed based on experimental data available from the literature to accurately obtain the moment-rotation results along the curve. The numerical models were verified with the moment-rotation curves of TSACs and the deformed shapes of the angles in the connections. The experimental results show that the finite element model in this study is adequate to predict the moment-rotation behavior of TSACs. The effects of bolt material properties, bolt diameter, bolt pretension load, friction coefficient, and gage distance on the moment-rotation behavior of the connections were investigated using the verified numerical model. The parametric analyses show that almost the same moment-rotation behavior is obtained for the connections by increasing the bolt strength and pretension load and varying the friction coefficients. The ultimate moment capacity of the connections was increased with a decrease in the gage distance.
Keywords: top and seat angle connection; finite element analysis; moment-rotation behavior; initial stiffness; ultimate moment; MOMENT; Construction & Building Technology; Engineering